Cytogenetic risk classification maintains its prognostic significance in transplanted FLT3‐ITD mutated acute myeloid leukemia patients: On behalf of the acute leukemia working party/European society of blood and marrow transplantation. Issue 3 (3rd January 2022) - Nagler, Arnon; Labopin, Myriam; Craddock, Charles; Socié, Gerard; Yakoub‐Agha, Ibrahim; Gedde‐Dahl, Tobias; Niittyvuopio, Riitta; Byrne, Jennifer Louise; Cornelissen, Jan J.; Labussière‐Wallet, Hélène; Arcese, William; Milpied, Noel; et al.
Abstract: FMS‐like tyrosine kinase 3 internal tandem duplication ( FLT3‐ITD ) mutational status is a pivotal prognosticator in acute myeloid leukemia (AML) patients and significantly increases the risk of disease relapse. However, it remains unclear whether in FLT3‐ITD patients referred for allogeneic stem cell transplantation (allo‐SCT), baseline cytogenetics significantly impacts clinical outcome. Using the European Society of Blood and Marrow Transplantation registry, we performed a retrospective analysis of 1631 FLT3‐ITD AML patients who underwent allo‐SCT with the aim of determining the influence of cytogenetic risk category on patient outcomes. Median patient age was 49 years and median follow‐up duration was 36 months. Two‐year leukemia‐free survival (LFS) and incidence of relapse were 54% and 31.6%, respectively. Non‐relapse mortality was experienced by 14.4% with a 2‐year overall survival (OS) of 60.1%. On multivariate analysis, LFS was significantly lower in patients with intermediate and adverse risk cytogenetics compared with those with favorable risk cytogenetics, (hazard ratio [HR] = 1.48, 95% confidence interval [CI], 1.06–2.06; p  = .02), and (HR = 01.65, 95% CI, 1.13–2.40; p  = .009), respectively. OS was significantly lower in patients with adverse risk cytogenetics compared with patients with favorable risk cytogenetics (HR = 1.74, 95% CI, 1.16–2.61; p  = .008) with a trend toward lower OS in patients with intermediate risk cytogenetics compared to those with favorable risk cytogenetics (HR = 1.43, 95% CI, 1.00–2.05; p  = .052). In addition, adverse risk patients and intermediate risk patients experienced higher relapse rates compared with favorable risk patients (HR = 1.83, 95% CI, 1.13–2.94; p  = .013 and HR = 1.82, 95% CI, 1.19–2.77; p  = .005). Overall, cytogenetic studies aid in refinement of risk stratification in transplanted FLT3‐ITD AML patients.